2020
DOI: 10.1111/cmi.13271
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium berghei sporozoites in nonreplicative vacuole are eliminated by a PI3P ‐mediated autophagy‐independent pathway

Abstract: The protozoan parasite Plasmodium, causative agent of malaria, invades hepatocytes by invaginating the host cell plasma membrane and forming a parasitophorous vacuole membrane (PVM). Surrounded by this PVM, the parasite undergoes extensive replication. Parasites inside a PVM provoke the Plasmodium-associated autophagyrelated (PAAR) response. This is characterised by a long-lasting association of the autophagy marker protein LC3 with the PVM, which is not preceded by phosphatidylinositol 3-phosphate (PI3P)-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…It should be noted that CT‐deficient mutant sporozoites can accumulate inside TVs, resulting in an apparent increase in total invasion events, although productive invasion is not affected (Risco‐Castillo et al, 2015; Steel et al, 2018), thus, making it difficult to distinguish between both invasion modes. Of note, the formation of TVs has been documented with P. yoelii and P. berghei sporozoites, in both hepatic and nonhepatic cells (Bindschedler et al, 2020; Risco‐Castillo et al, 2015), but has not been reported so far with P. falciparum . While the presence of a membrane surrounding intracellular sporozoites is insufficient to discriminate between TVs and PVs, the exclusion of host membrane proteins from the vacuole membrane is a distinctive feature of PVs (Risco‐Castillo et al, 2015).…”
Section: Challenges In Studying Plasmodium Sporozoite Invasionmentioning
confidence: 97%
“…It should be noted that CT‐deficient mutant sporozoites can accumulate inside TVs, resulting in an apparent increase in total invasion events, although productive invasion is not affected (Risco‐Castillo et al, 2015; Steel et al, 2018), thus, making it difficult to distinguish between both invasion modes. Of note, the formation of TVs has been documented with P. yoelii and P. berghei sporozoites, in both hepatic and nonhepatic cells (Bindschedler et al, 2020; Risco‐Castillo et al, 2015), but has not been reported so far with P. falciparum . While the presence of a membrane surrounding intracellular sporozoites is insufficient to discriminate between TVs and PVs, the exclusion of host membrane proteins from the vacuole membrane is a distinctive feature of PVs (Risco‐Castillo et al, 2015).…”
Section: Challenges In Studying Plasmodium Sporozoite Invasionmentioning
confidence: 97%
“…postinfection (Figure 3) [43,44]. Two studies based on live imaging highlighted that Plasmodium yoelii (Py) and Pb sporozoites form a transient vacuole (TV) during CT [44,45]. The acidification of the TV is believed to activate the micronemal perforin-like protein 1 (PLP1/Spect2), which lyses the TV membrane and might also subsequently wound the plasma membrane at the exit point [44].…”
Section: Box 2 Biogenesis and Exocytosis Of Micronemes And Rhoptries In Sporozoitesmentioning
confidence: 99%
“…The acidification of the TV is believed to activate the micronemal perforin-like protein 1 (PLP1/Spect2), which lyses the TV membrane and might also subsequently wound the plasma membrane at the exit point [44]. PLP1 mutants remain trapped in the TV and are degraded by proteases delivered upon the fusion of lysosomes with the TV [44,45]. CelTOS, known to have an important role in CT [20,21] partially dependent on its function in motility [21], is also suggested to be involved in cell membrane disruption after egressing the TV, as it displays pore-forming capabilities [46].…”
Section: Box 2 Biogenesis and Exocytosis Of Micronemes And Rhoptries In Sporozoitesmentioning
confidence: 99%
“…They allow the parasite (i) to escape hepatocyte elimination strategies, and (ii) to use host cell nutrients and develop alternative scavenging pathways for its survival [ 5 , 6 , 35 , 36 ]. As summarized in Figure 1 A, the following two host cell pathways for clearing the parasite are triggered during Pb A sporozoite development in the liver: (1) in the early intrahepatic stage, parasites inside a TV, or in a deficient PV, are cleared by the induction of a PI3P-associated sporozoite elimination (PASE) process that differs from autophagy, but induces a lysosomal acidification pathway; (2) in the late intrahepatic stage, the PV membrane (PVM) engulfed parasite is targeted by LAP-like non-conventional autophagy that occurs independently of PI3K, RB1-inducible coiled-coil 1 (Rb1cc1), and Ulk1, and without the formation of reactive oxygen species (ROS) ( Figure 1 A) [ 37 , 38 , 39 , 40 ]. The absence of PI3K and Becn1 (beclin 1, autophagy related) in this process argues in favor of the involvement of alternative non-canonical autophagy, distinct from LAP, in the elimination of the parasite during this late hepatic stage [ 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%